2019
DOI: 10.1007/s13238-019-00674-w
|View full text |Cite
|
Sign up to set email alerts
|

USP47-mediated deubiquitination and stabilization of YAP contributes to the progression of colorectal cancer

Abstract: w) contains supplementary material, which is available to authorized users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…The role of USP47 in cancer is cancer type-dependent. It can function as an oncoprotein in gastric cancer 49 , colorectal 29 , 30 , ovarian cancer 50 , and a tumor suppressor in medulloblastoma 36 . Our study reveals that USP47 is essential in the pathogenesis of CML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of USP47 in cancer is cancer type-dependent. It can function as an oncoprotein in gastric cancer 49 , colorectal 29 , 30 , ovarian cancer 50 , and a tumor suppressor in medulloblastoma 36 . Our study reveals that USP47 is essential in the pathogenesis of CML.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other USPs, USP47 regulates cellular activities by removing ubiquitin conjugates from diverse substrates and, thereby, altering their stabilities, localizations, or activities. Specifically, USP47 deubiquitinates and stabilizes MAPK 25 , DNA polymerase β (Polβ) 26 , E-cadherin 27 , β-catenin 28 , SNAIL 29 , YAP 30 , β-Trcp 31 , and katanin-p60 32 . Hence, USP47 is involved in cell proliferation 33 , cell survival 31 , DNA damage repair 26 , NLRP3 inflammasome activation 34 , and epithelial-mesenchymal transition 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Yes-associated protein (YAP) is one of the key downstream factors of the Hippo signaling pathway and is not only vital in the dynamic balance and development of tissue but also promotes tumorigenesis and participates in tumor development and metastasis [64]. Some studies have shown that YAP is involved in the biological behavior of pancreatic ductal adenocarcinoma, breast cancer, and rectal cancer [65][66][67]. TRAF6 promotes the malignant phenotype of pancreatic cancer by regulating YAP signaling [68] (Fig.…”
Section: Traf6 and Yap Pathwaymentioning
confidence: 99%
“…In breast cancer, USP9X deubiquitinates and stabilizes YAP to promote breast cancer cell proliferation and chemoresistance to therapeutic drugs [47]. USP47 functions as a DUB for YAP in colorectal cancer, USP47 elevation leads to stabilization of YAP and promotes colorectal cancer cell proliferation [48]. DUB3 regulates the protein stability of multiple components of Hippo pathway, including the LATS kinases, the E3 ligase ITCH and the AMOT family proteins, which in turn induces YAP turnover [49].…”
Section: Discussionmentioning
confidence: 99%